Experimental study on the permeability evolution of coal with CO2 phase transition. (1st March 2023) - Yao, Hongbo; Chen, Yuedu; Liang, Weiguo; Li, Zhigang; Song, Xiaoxia
Abstract: For CO2 sequestration in the deep coal seam, whose permeability would change with the CO2 phase transition. To evaluate this, a large size (Φ100 × 800 mm) raw coal sample, was used to conduct the permeability tests under varying CO2 injection pressures. With the increase of injection pressure, the phase transition of CO2 from subcritical (SubCO2 ) to supercritical (ScCO2 ) would alter pressure distribution within the coal, obviously reducing the internal permeability. For SubCO2 injection, the internal permeability decreases nonlinearly along the migration path, and the maximum occurs at the inlet, mainly where the effective stress is larger. However, for ScCO2 injection, the internal permeability forms a "U" shape, and the minimum occurs in the phase transition region, whose effect is greater than its effective stress. Due to the presence of phase transition, a "W" shape variation of CO2 permeability changes with the increasing pore pressure occurs. The CO2 phase transition would affect the coal structure significantly, the pore volume of coal reduced by ScCO2 adsorption is 28.07%, larger than that of 2.63% for SubCO2 . This irreversible change reduces the coal permeability by more than 63.3%. This study is meaningful to CO2 sequestration in deep coal seams. Highlights: CO2 flow in a large raw coal sample (Φ100 × 800 mm) was tested for the first time. Internal permeability evolution during the CO2 phase transition was characterized. A lower coal permeability was found within the CO2 phase transition region. Higher CO2 pore pressure brings lower permeability in CO2 transition region.